Uneven use of biodiversity indicators in 5th National Reports to the Convention on Biological Diversity. (10th December 2019) - Bhatt, Rashi; Gill, Michael J.; Hamilton, Healy; Han, Xuemei; Linden, Helaine M.; Young, Bruce E.
Summary: Indicators are necessary to monitor national progress toward commitments made to the Convention on Biological Diversity (CBD), but countries often struggle to mobilize quantitative indicators for many biodiversity targets. Assessing the extent to which countries are using measurable indicators from global and national sources by surveying 5th National Reports to the CBD, we found that nationally generated indicators were used 11 times more frequently than global indicators and only one-fifth of indicators matched those recommended by the CBD, suggesting that countries and indicator experts should work more closely to agree upon measurable, scalable, fit-for-purpose indicators for the next generation of CBD targets.